Target Spot Control and Modulation of the Physiology in Cucumber Using Phosphites and Chitosan - Fischer, Ivan Herman; Meleiro da Silva, Lucas; Marques de Almeida Bertani, Rosemary; Fernandes Deus, Angélica Cristina [UNESP]; Mota da Silva, Vicente [UNESP]; de Almeida Silva, Marcelo [UNESP] (My University, 2021)
Phosphites and chitosan were evaluated in target spot control, nutrition and gas exchange in cucumbers. Three weekly sprayings of commercial products were conducted, and Corynespora cassiicola (causal agent of target spot) was inoculated in the second and third true leaves four days after the last spraying. Zn, Mn, K and Cu phosphites reduced the disease severity, but the treatments had no effect on the development of the plants and the accumulation of macronutrients in the above ground part, with the exception of sulfur. The accumulation of Cu, Mn and Zn micronutrients were higher in plants treated with Cu, Mn and Zn phosphites, respectively. The green color index was influenced by the treatments after pathogen inoculation, with the highest values for Zn and Cu phosphites. Before inoculation, the products influenced net CO2 assimilation rate (A), stomatal conductance (gs) and internal CO2 concentration (Ci). The parameters gs and Ci increased, which indicates that the treatments can physiologically benefit the plants in the absence of a stress condition. After fungal inoculation, the Cu, Mn and Zn phosphites caused positive physiological effects, leading to the highest A values and adequate carboxylation efficiency (CE), which increases the capacity of plants to assimilate CO2. These phosphites also maintained adequate water use efficiency and gs and Ci values. Such indexes corresponded to lower disease severity, indicating that Mn, Zn and Cu phosphites reduced the stress caused by the disease, preserving the functionality of the photosynthetic apparatus.
Keywords: Alternative control; Corynespora cassiicola; Cucumis sativus; Disease severity; Gas exchange